Analisis Perilaku Konsumtif Belanja Online Aplikasi Tokopedia Pada Pekerja di Kota Surabaya - Muslimah, Izzah Asyanti; Nur, Dhani Ichsanuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Motivation for shopping is not solely driven by the need to fulfill basic necessities but also by the desire to satisfy personal wants. This issue is further intensified by the easy access to e-commerce platforms like Tokopedia, which offer a wide range of products. Individuals with higher incomes may be more susceptible to consumerist behavior when shopping online. This research seeks to investigate the impact of lifestyle, the use of digital wallets (e-wallets), and self-control on consumer behavior in online shopping through the Tokopedia app among workers in Surabaya City The research uses a quantitative method, employing a Likert scale for data measurement. Probability sampling with simple random sampling is the technique applied, yielding a sample of 94 respondents. Data analysis was conducted using Partial Least Squares (PLS) with SmartPLS 4 software, which involved validity testing, reliability testing, structural model analysis, and hypothesis testing. The results of the study show that lifestyle significantly influences consumerist behavior in online shopping through the Tokopedia app among workers in Surabaya City. However, the use of digital wallets (e-wallets) does not contribute to consumerist behavior in online shopping through the Tokopedia app among these workers, and self-control significantly influences consumerist behavior in online shopping through the Tokopedia app among workers in Surabaya City.